Law No. 16 of the year 2017 On Granting A Special Raise To The State Civil Servants Who Are Not Addressed with the Civil Service Law = قانون رقم 16 لسنة 2017 بمنح علاوة خاصة للعاملين بالدولة من غير المخاطبين بقانون الخدمة المدنية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic